IMMU-19. EVALUATING EFFECTS OF REVERSING DISTINCT FACETS OF IMMUNOSUPPRESSION IN EXPERIMENTAL GBM. (12th November 2021) - Ayasoufi, Katayoun; Tritz, Zachariah; Fain, Cori; Khadka, Roman; Jin, Fang; Hansen, Michael; Johnson, Aaron
Abstract: Glioblastoma is associated with severe and multifaceted immunosuppression affecting all immune organs. Immunosuppression in GBM is a critical barrier to the success of immunotherapies and patient survival. We demonstrated that immunosuppression in the GL261-model of experimental GBM presents with significant thymic and spleen atrophy, MHCII downregulation, presence of potent immunosuppressive factors in serum, and sequestration of T-cells in the bone marrow. Parabiosis studies determined that soluble factors mediate immunosuppression by inhibiting T-cell proliferation, thymic involution, and loss of peripheral T-cells. In contrast, bone marrow T-cell sequestration was not mediated through soluble factors. While the immunosuppression in GBM is severe, a causative link between each facet of immunosuppression and overall survival is lacking. We used two strategies to block T-cell sequestration into the bone marrow and evaluated the extent survival was impacted in experimental GBM. First, we evaluated the extent a novel and off-the-shelf combination immunotherapy that uses extended 1/2-life IL-2 and anti-PD-1 reverses bone marrow T-cell sequestration. Sham treatment or anti-PD1 monotherapy did not alter T-cell sequestration in the bone marrow and animals had no enhanced survival. Extended 1/2-life IL-2 monotherapy and combination strategy both prevented T-cell sequestration into the bone marrow. However, only combined therapy, which also prevented MHC class II downregulation, improved survival. Second, we determined that glioma-bearing adrenalectomized mice do not present with bone marrow T-cell sequestration. However, sera of glioma-bearing adrenalectomized mice is as immunosuppressive as glioma-bearing controls. Blocking bone marrow T-cell sequestration in the presences of serum immunosuppression led to no survival benefit in glioma-bearing adrenalectomized mice compared to controls. In short, bone marrow T-cell sequestration alone does not correspond with overall survival in experimental glioma. Importantly, a concerted effort to reverse MHC class II downregulation and define inhibitory circulating factors may have the highest impact in immunotherapeutic efficacy and improving patient survival.